Three-dimensional nanointerlocking structure recycled aluminum matrix composite material and preparation method thereof

CN120606083BActive Publication Date: 2026-11-03SHANDONG INNOVATION PRECISION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510683698.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2026-11-03
Estimated Expiration
2045-05-26

AI Technical Summary

Technical Problem

Traditional recycled aluminum production processes suffer from material performance degradation due to impurities after multiple cycles, low impurity separation efficiency, high aluminum burn-off rate, and technical barriers in high-end application fields. Existing processes have stringent requirements for waste aluminum raw materials, making it difficult to achieve high-value utilization of high-impurity content.

Method used

A three-dimensional nano-interlocked structure was constructed by employing steps such as multi-stage eddy current separation, X-ray fluorescence separation, liquid nitrogen cryogenic crushing, plasma-assisted ball milling, discharge plasma sintering, and microwave field treatment. In the recycled aluminum-based composite material, TiH2/B2O3 nanosheets react to generate TiB2 nanowires, which form an interlocked structure with Al2O3 nanosheets. Combined with Sc/Y composite powder, the interfacial energy was reduced, and the performance was improved by shot peening and rolling.

Benefits of technology

It achieves efficient separation of impurities, reduces interfacial energy, enhances mechanical properties, improves material density and fatigue strength, and is suitable for high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005419996560000081
    Figure BDA0005419996560000081
  • Figure BDA0005419996560000091
    Figure BDA0005419996560000091
Patent Text Reader

Abstract

The application provides a three-dimensional nanometer interlocking structure recycled aluminum-based composite material and a preparation method thereof. The preparation method is as follows: S1: waste aluminum sorting and crushing to obtain aluminum crushed material with a particle size of less than or equal to 5 mm; S2: plasma-assisted ball milling to obtain Al-Fe-Si nanometer composite powder; S3: taking 3.5 wt.% TiH2, 1.2-1.5 wt.% B2O3 nanometer sheet, 0.05-0.07 wt.% graphene, 0.25 wt.% Sc / Y composite powder and the rest recycled aluminum powder to mix wet grinding, and forming a porous preform through cold isostatic pressing; S4: placing the preform in a mold, preheating to 600 DEG C in a microwave field, discharging plasma sintering, and synchronously applying a pulse magnetic field; S5: adopting atmospheric plasma spraying to deposit an Al-Si coating, and then using a numerical control grinding machine to carry out mirror polishing; S6: carrying out shot peening treatment, and then carrying out one-pass rolling at room temperature, and carrying out aging treatment at 180 DEG C for 12 h, and the three-dimensional nanometer skeleton is constructed in situ. TiH2 / B2O3 nanometer sheet reacts in the sintering process to generate TiB2 nanometer wire and Al2O3 nanometer sheet to form an interlocking structure, and the mechanical properties are greatly enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of recycled aluminum alloy materials technology, specifically to a three-dimensional nano-interlocking structure recycled aluminum-based composite material and its preparation method. Background Technology

[0002] With the increasing global demand for aluminum resource recycling, the recycled aluminum industry faces an urgent need to transform from low-end recycling to high-value utilization. Traditional recycled aluminum production processes suffer from three major technical bottlenecks: First, impurity elements (Fe, Si, etc.) form harmful phases after multiple cycles, leading to a sharp deterioration in material properties. For example, in A380 recycled aluminum alloy, the elongation drops below 3% when the Fe content exceeds 0.8%. Second, existing sorting technologies struggle to achieve efficient separation of micron-sized impurities. Eddy current sorting has an efficiency of less than 70% for non-ferrous metals <0.5mm, and X-ray sorting speed is limited to below 3 tons / hour. Third, traditional smelting processes (>750℃) result in aluminum burn-off rates as high as 8-12%, and cannot eliminate brittle phases such as β-AlFeSi.

[0003] In existing technologies, mechanical ball milling followed by hot pressing sintering is used to prepare recycled aluminum-based composite materials, but the interfacial bonding between the reinforcing phase and the matrix is ​​poor (interfacial energy > 1.5 J / m). 2 Other methods include adding Sc microalloying to improve performance, but this does not solve the problem of harmful Fe / Si impurity phases; low-temperature electromagnetic stirring processes have also been proposed, but the grain size is still >20μm. Particularly noteworthy is the stringent requirement of traditional waste aluminum raw materials (Fe≤0.3%), resulting in over 90% of low-grade waste aluminum being downgraded for reuse. Under the dual-carbon strategy, there is an urgent need to develop high-value recycling technologies for recycled aluminum that are compatible with high impurity content, have short processes, and low energy consumption, breaking through the technological barriers in high-end application fields. Summary of the Invention

[0004] Technical problem to be solved: In view of the above-mentioned technical problems, the purpose of this invention is to provide a three-dimensional nano-interlocked structure recycled aluminum-based composite material and its preparation method. The three-dimensional nano-framework is constructed through in-situ reaction: TiH2 / B2O3 nanosheets react during sintering, and the generated TiB2 nanowires form an interlocked structure with Al2O3 nanosheets, which greatly enhances its mechanical properties.

[0005] Technical solution: A method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material, comprising the following steps:

[0006] S1: Waste aluminum sorting and crushing: Multi-stage eddy current sorting is used to remove particles ≥0.5mm; then X-ray fluorescence online sorting is used to classify the Fe / Si content of the sorted aluminum material, controlling Fe≤0.8% and Si≤0.5%; then liquid nitrogen cryogenic crushing is used to obtain aluminum scrap with a particle size ≤5mm.

[0007] S2: Plasma-assisted ball milling: Al-Fe-Si nanocomposite powder is obtained by simultaneous high-energy ball milling and radio frequency plasma treatment in an Ar / H2 atmosphere;

[0008] S3: Take 3.5wt.% TiH2, 1.2-1.5wt.% B2O3 nanosheets, 0.05-0.07wt.% graphene, 0.25wt.% Sc / Y composite powder and the balance recycled aluminum powder, mix them, use ethanol as medium, wet grind in a planetary ball mill for 3-4 hours, and form a porous preform by cold isostatic pressing;

[0009] S4: Place the preform in the mold, preheat it to 600°C in a microwave field, sinter it with discharge plasma, and simultaneously apply a 5-10T pulsed magnetic field;

[0010] S5: A 10μm thick Al-Si coating is deposited by atmospheric plasma spraying, followed by mirror polishing using a CNC grinding machine;

[0011] S6: After shot peening, it is rolled once at room temperature and aged at 180℃ for 12 hours to obtain the final product.

[0012] Furthermore, the multi-stage eddy current separation in S1 specifically consists of: the first stage: 1-3kHz low-frequency eddy current separation of non-ferrous metal particles >2mm; and the second stage: 10-15kHz high-frequency eddy current separation of fine impurity particles 0.5-2mm.

[0013] Furthermore, in S2, the ball milling speed is 500 rpm; the radio frequency plasma conditions are 10.56 MHz and 300 W.

[0014] Furthermore, in S3, the wet grinding ball ratio is 10:1, and the cold isostatic pressing is 200MPa.

[0015] Furthermore, in the S3 Sc / Y composite powder, the mass ratio of Sc to Y is 3:(1-2).

[0016] Furthermore, in S4, the preheating rate is 50℃ / s; and the pulse magnetic field frequency is 1Hz.

[0017] Furthermore, the discharge plasma sintering conditions in S4 are: temperature 1350℃, pressure 80MPa, pulse current 5000A, pulse width 3ms, interval 1ms, and holding time 5s.

[0018] Furthermore, the spray deposition material in S5 is Al-12Si powder with a particle size of 15-45μm; the spray deposition process is: power 40kW, spray distance 100mm, deposition rate 30μm / min.

[0019] Furthermore, the shot peening speed in S6 is 80 m / s.

[0020] The three-dimensional nano-interlocked structure of the recycled aluminum-based composite material prepared by the above method.

[0021] Beneficial effects:

[0022] 1. This invention utilizes the synergistic effect of low-frequency (1-3kHz) and high-frequency (10-15kHz) eddy currents and the differences in conductivity and permeability of different metals to achieve gradient separation of large particles (>2mm) and small particles (0.5-2mm) impurities, thereby improving sorting efficiency.

[0023] 2. This invention employs a plasma-mechanical synergistic nano-sizing effect: high-energy electrons generated by radio frequency plasma improve ball milling efficiency through the synergistic effect of surface sputtering and hydrogen permeation, while the plasma thermal effect promotes the dissolution and re-precipitation of the Fe3Si phase, forming a 50-100nm nano-dispersed phase.

[0024] 3. This invention constructs a three-dimensional nanoframework through in-situ reaction: TiH2 / B2O3 nanosheets react during sintering, and the generated TiB2 nanowires form an interlocking structure with the Al2O3 nanosheets, which greatly enhances their mechanical properties.

[0025] 4. This invention uses a pulsed magnetic field to eliminate pores and form a dense surface structure.

[0026] 5. In this invention, Sc segregates at the Al / TiB2 interface, reducing the interfacial energy, and the Y element stabilizes the interphase spacing of the nanoprecipitates at 50-80 nm by suppressing the coarsening of the Al3Sc phase.

[0027] 6. In this invention, the dislocation density introduced by shot peening and the shear band generated by rolling (20% deformation) work together to form a fine grain layer on the surface through dynamic recrystallization, thereby improving fatigue strength.

[0028] 7. When the present invention is aged at 180°C, the nucleation rate and growth rate of the Al3Sc phase reach equilibrium, so that the strength-plasticity are maintained in the best match. Detailed Implementation

[0029] This invention proposes a three-dimensional nano-interlocked structure recycled aluminum-based composite material and its preparation method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the following will provide a more detailed description of the invention with reference to specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0030] Example 1

[0031] A method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material includes the following steps:

[0032] S1: Waste aluminum sorting and crushing: Multi-stage eddy current sorting is adopted. The first stage: 2kHz low-frequency eddy current separation of non-ferrous metal particles >2mm; the second stage: 15kHz high-frequency eddy current separation of fine impurity particles 0.5-2mm; then X-ray fluorescence online sorting is used to classify the Fe / Si content of the sorted aluminum material, controlling the Fe content to 0.75% and the Si content to 0.45%; finally, aluminum scrap with a particle size ≤5mm is obtained by deep cryogenic crushing with liquid nitrogen.

[0033] S2: Plasma-assisted ball milling: Al-Fe-Si nanocomposite powder was obtained by ball milling at 500 rpm for 4 hours in an Ar / H2 (4:1) atmosphere and simultaneous treatment with radio frequency plasma at 10.56 MHz and 300 W.

[0034] S3: Mix 3.5 wt.% TiH2, 1.4 wt.% B2O3 nanosheets, 0.06 wt.% graphene, 0.25 wt.% Sc / Y composite powder and the balance recycled aluminum powder. Use ethanol as the medium and wet-mill in a planetary ball mill at a ball-to-material ratio of 10:1 for 4 hours. Then, cold isostatically press at 200 MPa to form a porous preform. The mass ratio of Sc to Y in the Sc / Y composite powder is 3:1.5.

[0035] S4: Place the preform in the mold, preheat it to 600℃ in a microwave field at a heating rate of 50℃ / s, and sinter it with discharge plasma at a temperature of 1350℃, a pressure of 80MPa, a pulse current of 5000A, a pulse width of 3ms, an interval of 1ms, a holding time of 5s, and simultaneously apply a 10T pulsed magnetic field with a frequency of 1Hz.

[0036] S5: An Al-Si coating with a thickness of 10μm is deposited by atmospheric plasma spraying. The spraying material is Al-12Si powder with a particle size of 15-45μm. The spraying deposition process is as follows: power 40kW, spraying distance 100mm, deposition rate 30μm / min, followed by mirror polishing with a CNC grinding machine.

[0037] S6: Perform shot peening at a speed of 80 m / s, roll once at room temperature with a rolling deformation of 20%, and age at 180℃ for 12 h to obtain the final product.

[0038] Example 2

[0039] A method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material includes the following steps:

[0040] S1: Waste aluminum sorting and crushing: Multi-stage eddy current sorting is adopted. The first stage: 2kHz low-frequency eddy current separation of non-ferrous metal particles >2mm; the second stage: 15kHz high-frequency eddy current separation of fine impurity particles 0.5-2mm; then X-ray fluorescence online sorting is used to classify the Fe / Si content of the sorted aluminum material, controlling the Fe content to 0.75% and the Si content to 0.45%; finally, aluminum scrap with a particle size ≤5mm is obtained by deep cryogenic crushing with liquid nitrogen.

[0041] S2: Plasma-assisted ball milling: Al-Fe-Si nanocomposite powder was obtained by ball milling at 500 rpm for 4 hours in an Ar / H2 (4:1) atmosphere and simultaneous treatment with radio frequency plasma at 10.56 MHz and 300 W.

[0042] S3: Mix 3.5 wt.% TiH2, 1.4 wt.% B2O3 nanosheets, 0.06 wt.% graphene, 0.25 wt.% Sc / Y composite powder and the balance recycled aluminum powder. Use ethanol as the medium and wet-mill in a planetary ball mill at a ball-to-material ratio of 10:1 for 4 hours. Then, cold isostatically press at 200 MPa to form a porous preform. The mass ratio of Sc to Y in the Sc / Y composite powder is 3:1.

[0043] S4: Place the preform in the mold, preheat it to 600℃ in a microwave field at a heating rate of 50℃ / s, and sinter it with discharge plasma at a temperature of 1350℃, a pressure of 80MPa, a pulse current of 5000A, a pulse width of 3ms, an interval of 1ms, a holding time of 5s, and simultaneously apply a 10T pulsed magnetic field with a frequency of 1Hz.

[0044] S5: An Al-Si coating with a thickness of 10μm is deposited by atmospheric plasma spraying. The spraying material is Al-12Si powder with a particle size of 15-45μm. The spraying deposition process is as follows: power 40kW, spraying distance 100mm, deposition rate 30μm / min, followed by mirror polishing with a CNC grinding machine.

[0045] S6: Perform shot peening at a speed of 80 m / s, roll once at room temperature with a rolling deformation of 20%, and age at 180℃ for 12 h to obtain the final product.

[0046] Example 3

[0047] A method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material includes the following steps:

[0048] S1: Waste aluminum sorting and crushing: Multi-stage eddy current sorting is adopted. The first stage: 2kHz low-frequency eddy current separation of non-ferrous metal particles >2mm; the second stage: 15kHz high-frequency eddy current separation of fine impurity particles 0.5-2mm; then X-ray fluorescence online sorting is used to classify the Fe / Si content of the sorted aluminum material, controlling the Fe content to 0.75% and the Si content to 0.45%; finally, aluminum scrap with a particle size ≤5mm is obtained by deep cryogenic crushing with liquid nitrogen.

[0049] S2: Plasma-assisted ball milling: Al-Fe-Si nanocomposite powder was obtained by ball milling at 500 rpm for 4 hours in an Ar / H2 (4:1) atmosphere and simultaneous treatment with radio frequency plasma at 10.56 MHz and 300 W.

[0050] S3: Mix 3.5 wt.% TiH2, 1.4 wt.% B2O3 nanosheets, 0.06 wt.% graphene, 0.25 wt.% Sc / Y composite powder and the balance recycled aluminum powder. Use ethanol as the medium and wet mill in a planetary ball mill at a ball-to-material ratio of 10:1 for 4 hours. Then, cold isostatically press at 200 MPa to form a porous preform. The mass ratio of Sc to Y in the Sc / Y composite powder is 3:2.

[0051] S4: Place the preform in the mold, preheat it to 600℃ in a microwave field at a heating rate of 50℃ / s, and sinter it with discharge plasma at a temperature of 1350℃, a pressure of 80MPa, a pulse current of 5000A, a pulse width of 3ms, an interval of 1ms, a holding time of 5s, and simultaneously apply a 10T pulsed magnetic field with a frequency of 1Hz.

[0052] S5: An Al-Si coating with a thickness of 10μm is deposited by atmospheric plasma spraying. The spraying material is Al-12Si powder with a particle size of 15-45μm. The spraying deposition process is as follows: power 40kW, spraying distance 100mm, deposition rate 30μm / min, followed by mirror polishing with a CNC grinding machine.

[0053] S6: Perform shot peening at a speed of 80 m / s, roll once at room temperature with a rolling deformation of 20%, and age at 180℃ for 12 h to obtain the final product.

[0054] Example 4

[0055] A method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material includes the following steps:

[0056] S1: Waste aluminum sorting and crushing: Multi-stage eddy current sorting is adopted. The first stage: 2kHz low-frequency eddy current separation of non-ferrous metal particles >2mm; the second stage: 15kHz high-frequency eddy current separation of fine impurity particles 0.5-2mm; then X-ray fluorescence online sorting is used to classify the Fe / Si content of the sorted aluminum material, controlling the Fe content to 0.75% and the Si content to 0.45%; finally, aluminum scrap with a particle size ≤5mm is obtained by deep cryogenic crushing with liquid nitrogen.

[0057] S2: Plasma-assisted ball milling: Al-Fe-Si nanocomposite powder was obtained by ball milling at 500 rpm for 4 hours in an Ar / H2 (4:1) atmosphere and simultaneous treatment with radio frequency plasma at 10.56 MHz and 300 W.

[0058] S3: Mix 3.5 wt.% TiH2, 1.2 wt.% B2O3 nanosheets, 0.06 wt.% graphene, 0.25 wt.% Sc / Y composite powder, and the remainder recycled aluminum powder. Use ethanol as the medium and wet-mill in a planetary ball mill at a ball-to-material ratio of 10:1 for 4 hours. Then, cold isostatically press at 200 MPa to form a porous preform. The mass ratio of Sc to Y in the Sc / Y composite powder is 3:1.5.

[0059] S4: Place the preform in the mold, preheat it to 600℃ in a microwave field at a heating rate of 50℃ / s, and sinter it with discharge plasma at a temperature of 1350℃, a pressure of 80MPa, a pulse current of 5000A, a pulse width of 3ms, an interval of 1ms, a holding time of 5s, and simultaneously apply a 10T pulsed magnetic field with a frequency of 1Hz.

[0060] S5: An Al-Si coating with a thickness of 10μm is deposited by atmospheric plasma spraying. The spraying material is Al-12Si powder with a particle size of 15-45μm. The spraying deposition process is as follows: power 40kW, spraying distance 100mm, deposition rate 30μm / min, followed by mirror polishing with a CNC grinding machine.

[0061] S6: Perform shot peening at a speed of 80 m / s, roll once at room temperature with a rolling deformation of 20%, and age at 180℃ for 12 h to obtain the final product.

[0062] Example 5

[0063] A method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material includes the following steps:

[0064] S1: Waste aluminum sorting and crushing: Multi-stage eddy current sorting is adopted. The first stage: 2kHz low-frequency eddy current separation of non-ferrous metal particles >2mm; the second stage: 15kHz high-frequency eddy current separation of fine impurity particles 0.5-2mm; then X-ray fluorescence online sorting is used to classify the Fe / Si content of the sorted aluminum material, controlling the Fe content to 0.75% and the Si content to 0.45%; finally, aluminum scrap with a particle size ≤5mm is obtained by deep cryogenic crushing with liquid nitrogen.

[0065] S2: Plasma-assisted ball milling: Al-Fe-Si nanocomposite powder was obtained by ball milling at 500 rpm for 4 hours in an Ar / H2 (4:1) atmosphere and simultaneous treatment with radio frequency plasma at 10.56 MHz and 300 W.

[0066] S3: Mix 3.5 wt.% TiH2, 1.5 wt.% B2O3 nanosheets, 0.06 wt.% graphene, 0.25 wt.% Sc / Y composite powder, and the remainder recycled aluminum powder. Use ethanol as the medium and wet-mill in a planetary ball mill at a ball-to-material ratio of 10:1 for 4 hours. Then, cold isostatically press the mixture at 200 MPa to form a porous preform. The mass ratio of Sc to Y in the Sc / Y composite powder is 3:1.5.

[0067] S4: Place the preform in the mold, preheat it to 600℃ in a microwave field at a heating rate of 50℃ / s, and sinter it with discharge plasma at a temperature of 1350℃, a pressure of 80MPa, a pulse current of 5000A, a pulse width of 3ms, an interval of 1ms, a holding time of 5s, and simultaneously apply a 10T pulsed magnetic field with a frequency of 1Hz.

[0068] S5: An Al-Si coating with a thickness of 10μm is deposited by atmospheric plasma spraying. The spraying material is Al-12Si powder with a particle size of 15-45μm. The spraying deposition process is as follows: power 40kW, spraying distance 100mm, deposition rate 30μm / min, followed by mirror polishing with a CNC grinding machine.

[0069] S6: Perform shot peening at a speed of 80 m / s, roll once at room temperature with a rolling deformation of 20%, and age at 180℃ for 12 h to obtain the final product.

[0070] Example 6

[0071] A method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material includes the following steps:

[0072] S1: Waste aluminum sorting and crushing: Multi-stage eddy current sorting is adopted. The first stage: 2kHz low-frequency eddy current separation of non-ferrous metal particles >2mm; the second stage: 15kHz high-frequency eddy current separation of fine impurity particles 0.5-2mm; then X-ray fluorescence online sorting is used to classify the Fe / Si content of the sorted aluminum material, controlling the Fe content to 0.75% and the Si content to 0.45%; finally, aluminum scrap with a particle size ≤5mm is obtained by deep cryogenic crushing with liquid nitrogen.

[0073] S2: Plasma-assisted ball milling: Al-Fe-Si nanocomposite powder was obtained by ball milling at 500 rpm for 4 hours in an Ar / H2 (4:1) atmosphere and simultaneous treatment with radio frequency plasma at 10.56 MHz and 300 W.

[0074] S3: Mix 3.5 wt.% TiH2, 1.4 wt.% B2O3 nanosheets, 0.05 wt.% graphene, 0.25 wt.% Sc / Y composite powder and the balance recycled aluminum powder. Use ethanol as the medium and wet-mill in a planetary ball mill at a ball-to-material ratio of 10:1 for 4 hours. Then, cold isostatically press at 200 MPa to form a porous preform. The mass ratio of Sc to Y in the Sc / Y composite powder is 3:1.5.

[0075] S4: Place the preform in the mold, preheat it to 600℃ in a microwave field at a heating rate of 50℃ / s, and sinter it with discharge plasma at a temperature of 1350℃, a pressure of 80MPa, a pulse current of 5000A, a pulse width of 3ms, an interval of 1ms, a holding time of 5s, and simultaneously apply a 10T pulsed magnetic field with a frequency of 1Hz.

[0076] S5: An Al-Si coating with a thickness of 10μm is deposited by atmospheric plasma spraying. The spraying material is Al-12Si powder with a particle size of 15-45μm. The spraying deposition process is as follows: power 40kW, spraying distance 100mm, deposition rate 30μm / min, followed by mirror polishing with a CNC grinding machine.

[0077] S6: Perform shot peening at a speed of 80 m / s, roll once at room temperature with a rolling deformation of 20%, and age at 180℃ for 12 h to obtain the final product.

[0078] Example 7

[0079] A method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material includes the following steps:

[0080] S1: Waste aluminum sorting and crushing: Multi-stage eddy current sorting is adopted. The first stage: 2kHz low-frequency eddy current separation of non-ferrous metal particles >2mm; the second stage: 15kHz high-frequency eddy current separation of fine impurity particles 0.5-2mm; then X-ray fluorescence online sorting is used to classify the Fe / Si content of the sorted aluminum material, controlling the Fe content to 0.75% and the Si content to 0.45%; finally, aluminum scrap with a particle size ≤5mm is obtained by deep cryogenic crushing with liquid nitrogen.

[0081] S2: Plasma-assisted ball milling: Al-Fe-Si nanocomposite powder was obtained by ball milling at 500 rpm for 4 hours in an Ar / H2 (4:1) atmosphere and simultaneous treatment with radio frequency plasma at 10.56 MHz and 300 W.

[0082] S3: Mix 3.5 wt.% TiH2, 1.4 wt.% B2O3 nanosheets, 0.07 wt.% graphene, 0.25 wt.% Sc / Y composite powder and the balance recycled aluminum powder. Use ethanol as the medium and wet mill in a planetary ball mill at a ball-to-material ratio of 10:1 for 4 hours. Then, cold isostatically press at 200 MPa to form a porous preform. The mass ratio of Sc to Y in the Sc / Y composite powder is 3:1.5.

[0083] S4: Place the preform in the mold, preheat it to 600℃ in a microwave field at a heating rate of 50℃ / s, and sinter it with discharge plasma at a temperature of 1350℃, a pressure of 80MPa, a pulse current of 5000A, a pulse width of 3ms, an interval of 1ms, a holding time of 5s, and simultaneously apply a 10T pulsed magnetic field with a frequency of 1Hz.

[0084] S5: An Al-Si coating with a thickness of 10μm is deposited by atmospheric plasma spraying. The spraying material is Al-12Si powder with a particle size of 15-45μm. The spraying deposition process is as follows: power 40kW, spraying distance 100mm, deposition rate 30μm / min, followed by mirror polishing with a CNC grinding machine.

[0085] S6: Perform shot peening at a speed of 80 m / s, roll once at room temperature with a rolling deformation of 20%, and age at 180℃ for 12 h to obtain the final product.

[0086] Example 8

[0087] A method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material includes the following steps:

[0088] S1: Waste aluminum sorting and crushing: Multi-stage eddy current sorting is adopted. The first stage: 2kHz low-frequency eddy current separation of non-ferrous metal particles >2mm; the second stage: 15kHz high-frequency eddy current separation of fine impurity particles 0.5-2mm; then X-ray fluorescence online sorting is used to classify the Fe / Si content of the sorted aluminum material, controlling the Fe content to 0.75% and the Si content to 0.45%; finally, aluminum scrap with a particle size ≤5mm is obtained by deep cryogenic crushing with liquid nitrogen.

[0089] S2: Plasma-assisted ball milling: Al-Fe-Si nanocomposite powder was obtained by ball milling at 500 rpm for 4 hours in an Ar / H2 (4:1) atmosphere and simultaneous treatment with radio frequency plasma at 10.56 MHz and 300 W.

[0090] S3: Mix 3.5 wt.% TiH2, 1.4 wt.% B2O3 nanosheets, 0.06 wt.% graphene, 0.25 wt.% Sc / Y composite powder and the balance recycled aluminum powder. Use ethanol as the medium and wet-mill in a planetary ball mill at a ball-to-material ratio of 10:1 for 4 hours. Then, cold isostatically press at 200 MPa to form a porous preform. The mass ratio of Sc to Y in the Sc / Y composite powder is 3:1.5.

[0091] S4: Place the preform in the mold, preheat it to 600℃ in a microwave field at a heating rate of 50℃ / s, and sinter it with discharge plasma at a temperature of 1350℃, a pressure of 80MPa, a pulse current of 5000A, a pulse width of 3ms, an interval of 1ms, a holding time of 5s, and simultaneously apply a 5T pulsed magnetic field with a frequency of 1Hz.

[0092] S5: An Al-Si coating with a thickness of 10μm is deposited by atmospheric plasma spraying. The spraying material is Al-12Si powder with a particle size of 15-45μm. The spraying deposition process is as follows: power 40kW, spraying distance 100mm, deposition rate 30μm / min, followed by mirror polishing with a CNC grinding machine.

[0093] S6: Perform shot peening at a speed of 80 m / s, roll once at room temperature with a rolling deformation of 20%, and age at 180℃ for 12 h to obtain the final product.

[0094] Comparative Example 1

[0095] The difference between this embodiment and Embodiment 1 is that there is no plasma-assisted ball milling; only ordinary ball milling for 6 hours is used.

[0096] Comparative Example 2

[0097] The difference between this embodiment and Embodiment 1 is that TiH2 / B2O3 nanosheets are not added.

[0098] Comparative Example 3

[0099] The difference between this embodiment and Embodiment 1 is that only a pulsed magnetic field is used, and plasma assistance is eliminated.

[0100] Comparative Example 4

[0101] The difference between this embodiment and Embodiment 1 is that the mass ratio of Sc to Y in the Sc / Y composite powder is 5:1.

[0102] Tensile strength: ASTM E8 standard, universal testing machine, strain rate 1×10⁻⁶ 3 / s;

[0103] Elongation: Measured with a 50mm gauge length extensometer;

[0104] Hardness: Vickers hardness tester (HV1, load 1kgf, holding pressure 15s);

[0105] Thermal conductivity: Laser flare method (Netzsch LFA467);

[0106] Salt spray test: ASTM B117 standard, 5% NaCl solution, 35℃;

[0107] The results are shown in Table 1 below:

[0108] Table 1

[0109]

[0110]

Claims

1. A method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material, characterized in that, Includes the following steps: S1: Waste aluminum sorting and crushing: Multi-stage eddy current sorting is used to remove particles ≥0.5mm; then X-ray fluorescence online sorting is used to classify the Fe / Si content of the sorted aluminum material, controlling Fe≤0.8% and Si≤0.5%; then liquid nitrogen cryogenic crushing is used to obtain aluminum scrap with a particle size ≤5mm. S2: Plasma-assisted ball milling: Al-Fe-Si nanocomposite powder is obtained by simultaneous high-energy ball milling and radio frequency plasma treatment in an Ar / H2 atmosphere; S3: Take 3.5wt.%TiH2, 1.2-1.5wt.%B2O3 nanosheets, 0.05-0.07wt.%graphene, 0.25wt.%Sc / Y composite powder and the balance recycled aluminum powder, mix them, use ethanol as medium, wet grind in a planetary ball mill for 3-4 hours, and form a porous preform by cold isostatic pressing; S4: Place the preform in the mold, preheat it to 600°C in a microwave field, sinter it with discharge plasma, and simultaneously apply a 5-10T pulsed magnetic field; S5: A 10μm thick Al-Si coating is deposited by atmospheric plasma spraying, followed by mirror polishing using a CNC grinding machine; S6: After shot peening, it is rolled once at room temperature and aged at 180℃ for 12 hours to obtain the product. The mass ratio of Sc to Y in the Sc / Y composite powder in S3 is 3:(1-2).

2. The method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material according to claim 1, characterized in that, The multi-stage eddy current separation in S1 is specifically as follows: First stage: 1-3kHz low-frequency eddy current separation of non-ferrous metal particles >2mm; Second stage: 10-15kHz high-frequency eddy current separation of fine impurity particles 0.5-2mm.

3. The method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material according to claim 1, characterized in that, In S2, the ball milling speed is 500 rpm; the radio frequency plasma conditions are 10.56 MHz and 300 W.

4. The method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material according to claim 1, characterized in that, In S3, the wet grinding ball ratio is 10:1, and the cold isostatic pressing is 200MPa.

5. The method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material according to claim 1, characterized in that, The preheating rate in S4 is 50℃ / s; the pulse magnetic field frequency is 1Hz.

6. The method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material according to claim 1, characterized in that, The discharge plasma sintering conditions in S4 are: temperature 1350℃, pressure 80MPa, pulse current 5000A, pulse width 3ms, interval 1ms, and holding time 5s.

7. The method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material according to claim 1, characterized in that, The spray deposition material in S5 is Al-12Si powder with a particle size of 15-45 μm; the spray deposition process is: power 40kW, spray distance 100mm, deposition rate 30 μm / min.

8. The method for preparing a three-dimensional nano-interlocked structure recycled aluminum-based composite material according to claim 1, characterized in that, The shot peening speed in S6 is 80 m / s.

9. The three-dimensional nano-interlocking structure recycled aluminum-based composite material prepared by the method according to any one of claims 1-8.

Citation Information

Patent Citations

  • Three-dimensional carbon nanophase composite reinforced aluminum-based material and preparation method thereof

    CN111996418A

  • Process for producing graphene / silicon nanowire hybrid material for a lithium-ion battery

    WO2020154124A2